Characterization of Cobalt Sulfide Thin Films Synthesized from Acidic Chemical Baths - Tizazu Abza; Dereje Gelanu Dadi; Fekadu Gashaw Hone; Tesfaye Chebelew Meharu; Gebremeskel Tekle; Eyobe Belew Abebe; Kalid Seid Ahmed (Advances in Materials Science and Engineering)
Cobalt sulfide thin films were synthesized from acidic chemical baths by varying the deposition time. The powder X-ray diffraction studies indicated that there are hexagonal CoS, face-centered cubic Co3S4, and cubic Co9S8 phases of cobalt sulfide. The crystallite size of the hexagonal CoS phase decreased from 52.8 nm to 22.5 nm and that of the cubic Co9S8 phase increased from 11 nm to 60 nm as the deposition time increased from 2 hrs to 3.5 hrs. The scanning electron microscopic images revealed crack and pinhole free thin films with uniform and smooth background and few large polygonal grains on the surface. The band gap of the cobalt sulfide thin films decreased from 1.75 eV to 1.3 eV as the deposition time increased from 2 hrs to 3.5 hrs. The photoluminescence (PL) spectra of the films confirmed the emission of ultraviolet, violet, and blue lights. The intense PL emission of violet light at 384 nm had red shifted with increasing deposition time that could be resulted from the increase in the average crystallite size. The FTIR spectra of the films indicated the presence of OH, C-O-H, C-O, double sulfide, and Co-S groups. As the deposition time increased, the electrical resistivity of the cobalt sulfide thin films decreased due to the increase in both the crystallite size and the films’ thickness.